Is Foreign Aid Making A Difference? A Case Study of Sagarmatha National Park Forestry Project, Khumbu, Nepal - Bhatta, Chet; Bardecki, Michal (New Angle: Nepal Journal of Social Science and Public Policy, 2014)
This paper describes a community stakeholder approach to evaluating the effectiveness of foreign aid and NGO involvement in an impacted community. The focus of the study, the Sagarmatha National Park Forestry Project (SNPFP), has operated in the Khumbu region for more than thirty years. The success of foreign aid and NGO activities was assessed by interviewing key informants with regard to their experience and perceptions concerning the project. The implications of this study include the recommendation that local people are the best source of information to measure foreign aid and NGO performance in a remote community. Furthermore, the future of natural resource conservation and rural development led by foreign aid depends on collaboration between the local people, NGOs and government.